Complexity and Nonlinearity in Cardiovascular Signals 2017
DOI: 10.1007/978-3-319-58709-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Intermittency-Driven Complexity in Signal Processing

Abstract: In this chapter, we rst discuss the main motivations that are causing an increasing interest of many research elds and the interdisciplinary eort of many research groups towards the new paradigm of complexity. Then, without claiming to include all possible complex systems, which is much beyond the scope of this review, we introduce a possible denition of complexity. Along this line, we also introduce our particular approach to the analysis and modeling of complex systems. This is based on the ubiquitous observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 115 publications
(165 reference statements)
0
6
0
Order By: Relevance
“…Thus, the consequences of passing online probably include remediation mechanisms related to the use of the new digital technologies (Bolter and Grusin, 1999). These mechanisms are compatible with the self-organization paradigm of complexity: cooperative social dynamics between different individuals/groups trigger the emergence of a new dynamical equilibrium in a relatively short time due to an environmental change (in this case, the new digital technologies) (Zeleny, 1977;Santos et al, 2006;Paradisi et al, 2015;Paradisi and Allegrini, 2017;Mahmoodi et al, 2018). The equilibrium is constrained to the optimization of social interactivity mediated by the new technology, the optimum possibly being a condition as nearest as possible to live interactivity.…”
Section: Final Discussionmentioning
confidence: 70%
“…Thus, the consequences of passing online probably include remediation mechanisms related to the use of the new digital technologies (Bolter and Grusin, 1999). These mechanisms are compatible with the self-organization paradigm of complexity: cooperative social dynamics between different individuals/groups trigger the emergence of a new dynamical equilibrium in a relatively short time due to an environmental change (in this case, the new digital technologies) (Zeleny, 1977;Santos et al, 2006;Paradisi et al, 2015;Paradisi and Allegrini, 2017;Mahmoodi et al, 2018). The equilibrium is constrained to the optimization of social interactivity mediated by the new technology, the optimum possibly being a condition as nearest as possible to live interactivity.…”
Section: Final Discussionmentioning
confidence: 70%
“…With its capability to probe tissues with l D below the micrometer scale, transient anomalous diffusion (tAD) ( Capuani and Palombo, 2020 ) and its new local parameters would dramatically increase DMRI diagnostic potential in detecting collective, micro and sub-micro architectural changes of human tissues due to pathological damage. Anomalous diffusion ( Metzler and Klafter, 2000 ; Burov et al, 2011 ; Metzler et al, 2014 ; Chakraborty and Roichman, 2020 ) is ubiquitously observed in many complex biological systems, ranging from soft matter, e.g., the cell cytoplasm, membrane ( Saxton and Jacobson, 1997 ; Tolić-Nørrelykke et al, 2004 ; Golding and Cox, 2006 ; Zaid et al, 2009 ; Weigel et al, 2011 ; Javanainen et al, 2012 ; Hofling and Franosch, 2013 ; Honigmann et al, 2013 ; Jeon et al, 2016 ; Metzler et al, 2016 ; Pöschke et al, 2016 ) and, extracellular space (ECS) ( Sykovà and Nicholson, 2008 ; Sherpa et al, 2014 ; Nicholson, 2015 ; Xiao et al, 2015 ) to the nucleus ( Bronstein et al, 2009 ; Stadler and Weiss, 2017 ; Pierro et al, 2018 ) and neuro-physiological systems ( Allegrini et al, 2015 ; Paradisi and Allegrini, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Random times, also called waiting times (WTs), describe a trapping mechanism due to a sequence of potential wells [52,53], thus this particular CTRW model can describe only subdiffusion (φ < 1). The WT is the intermediate long time between two crucial short-time events, each one given by the escape from a given well and the jump into another one, thus CTRW is essentially driven by the sequence of WTs, described by a renewal point process [6,[54][55][56][57][58]. Several CTRW models have been introduced and investigated, but the subdiffusive CTRW remains probably the most studied and applied one, with the exception of socalled Lévy Walk (LW) model, which is a CTRW whose jumps and WTs are coupled [59][60][61].…”
Section: Introductionmentioning
confidence: 99%